Damage sensing in multi-functional glass fiber composites under mode-I fracture loading. (December 2020) - O'Donnell, Jacob; Chalivendra, Vijaya; Hall, Asha; Kim, Yong
A detailed experimental study is performed for piezo resistance damage sensing on conductive glass fiber/epoxy composites under mode-I fracture conditions. The conductive composites are fabricated by homogeneously dispersing carbon nanotubes (CNTs) within the epoxy matrix and electro-flocking short carbon fibers onto the laminates along with a vacuum infusion process. A parametric study is done on the in-situ damage sensing properties by varying the carbon fiber lengths (150 µm and 350 µm) and the carbon fiber areal densities (500, 1000, 1500, and 2000 fibers/mm 2 ). The change in resistance is captured with a four-point probe measuring methodology by measuring the resistance through the thickness of the composite. The crack initiation toughness value of the composites containing carbon fibers showed improvement over control composites. Composites containing 350 µm length carbon fibers and 2000 fiber/mm 2 not only showed the best crack initiation toughness but also provided sensitive network for detecting crack growth.